Optimization of chitosan gel preparation for supercritical impregnation of thymol - Milovanović Stoja L. (Tehnika, 2015)
The impregnation of differently prepared chitosan gels with thymol using supercritical carbon dioxide (scCO2) was studied in order to obtain new materials with added value without the use of organic solvents. The optimum conditions of supercritical impregnation (15 MPa, 35 °C and 24 h) were defined based on previously investigated thymol solubility in scCO2. Cross-linkers formaldehyde and glutardialdehyde were used to prepare chitosan hydrogels. The obtained hydrogels of chitosan were converted in acetogels and then dried with air or by using scCO2 in order to obtain xerogels and aerogels. The best results, in terms of morphology and yield of impregnation with thymol, have been achieved for the aerogel of chitosan (11.30%) which was obtained with cross-linker formaldehyde and dried with scCO2 at 15 MPa and 50 °C.